EnglishPenyembuhan Luka Diabetes Krim Biosurfaktan Dialkil Alginat pada Ekspresi TNF-α TGF-β, Reepitelisasi, dan Kolagenisasi - Cut Raihanah; Nurul Mahyani; Kintoko Kintoko (JURNAL ILMU KEFARMASIAN INDONESIA, 2019)
Diabetic wound healing is delayed by many factors, including high TNF-α expression and low TGF-β expression which can affect the formation of new epithelial tissue and collagen as the main goal of the wound healing process. One of the diabetic wound healing agent is biosurfactant dialkyl alginate where so far its use in cream form for diabetic wound has never been reported. This study aimed to determine TNF-α, TGF-β, reepithelization and the collagenization of biosurfactant dialkyl alginate cream in diabetic biopsy wounds in STZ-induced rat. Biosurfactant dialkyl alginate was made in cream form and applied to biopsy wounds on the backs of rat twice a day for 9 days. Observation of TNF-α and TGF-β expression were performed by immunohistochemical staining, while epithelial and collagen with staining HE and Mallory. The results showed that the biosurfactant dialkyl alginate cream had an activity to decrease TNF-α expression, increase TGF-β expression and reepithelization but did not have any significant activity on collagenization. These results suggest that the biosurfactant dialkyl alginate cream can accelerate the healing of diabetic wound.